2010
DOI: 10.2337/db09-0583
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I Bioactivity in an Elderly Population

Abstract: OBJECTIVEThere is a complex relationship between IGF-I, IGF binding proteins, growth hormone, and insulin. The IGF-I kinase receptor activation assay (KIRA) is a novel method for measuring IGF-I bioactivity in human serum. We speculated that determination of IGF-I bioactivity might broaden our understanding of the IGF-I system in subjects with the metabolic syndrome. The purpose of our study was to investigate whether IGF-I bioactivity was related to insulin sensitivity and the metabolic syndrome.RESEARCH DESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
6
19
0
Order By: Relevance
“…Further study is needed to identify sensitive biomarkers to monitor rhGH replacement therapy. Second, it is previously shown that there is an optimum for GH dosing with respect to insulin resistance (33). In this respect, further lowering of the GH dose is probably needed to minimize insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Further study is needed to identify sensitive biomarkers to monitor rhGH replacement therapy. Second, it is previously shown that there is an optimum for GH dosing with respect to insulin resistance (33). In this respect, further lowering of the GH dose is probably needed to minimize insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The somatotropic axis and its activity has claimed to be implicated both in healthy and non-healthy ageing, by virtue of which an improved or impaired IGF-I action may influence the development of diseases affecting longevity and survival with a U-shape effect [6,9]. In relation to this, circulating IGF-I levels in the upper normal range have been associated with a higher prevalence of prostate and colon cancer as well as increased muscle mass and muscle strength [20], while low levels are present in old and frail individuals with different degrees of disability [21] and premature mortality [7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inclusion of a younger sample of individuals would have overcome the problem of the overrepresentation of certain genotypes due to survival bias, and also, the current minority prevalence of non-carriers of 192 bp allele may have caused problems of statistical power in the sample. Additionally, the measurement of free IGF-I or IGF-I bioactivity [6,9] rather than total IGF-I would have helped to establish certain associations not found with the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older persons with metabolic syndrome are more likely to experience any CVD event than subjects without metabolic syndrome (7,8). In two previous studies on the association of IGF1 with the metabolic syndrome in older populations, U-shaped relationships have been reported (9,10). Others report low IGF1 values to be related to a greater metabolic burden (11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%